Retinal cell type‐specific prevention of ischemia‐induced damages by LPS‐TLR4 signaling through microglia. (13th May 2013) - Halder, Sebok K.; Matsunaga, Hayato; Ishii, Ken J.; Akira, Shizuo; Miyake, Kensuke; Ueda, Hiroshi
Abstract Reprogramming of toll‐like receptor 4 (TLR4) by brief ischemia or lipopolysacharide (LPS) contributes to superintending tolerance against destructive ischemia in brain. However, beneficial roles of TLR4 signaling in ischemic retina are not well known. This study demonstrated that preconditioning with LPS 48 h prior to the retinal ischemia prevents the cellular damage in morphology with hematoxylin and eosin (H&E) staining and functions of retina with electroretinogram (ERG), while post‐ischemia treatment deteriorated it. The preventive effects of LPS preconditioning showed the cell type‐specificity of retinal cells. There was complete rescue of ganglion cells, partial rescue of bipolar and photoreceptor cells or no rescue of amacrine cells, respectively. LPS treatment caused the proliferation and migration of retinal microglia and its preconditioning prevented the ischemia‐induced microglial activation. Preventive actions from cell damages following LPS preconditioning prior to retinal ischemia were abolished in TLR4 knock‐out mice, and by pre‐treatments with anti‐TLR4 antibody or minocycline, a microglia inhibitor, which themselves had no effects on the retinal ischemia‐induced damages or microglia activation. Thus, this study revealed that TLR4 mediates the LPS preconditioning‐induced preventive effects through microglial activation in the retinal ischemia model.